Free jejunal transfer for pharyngo-esophageal reconstruction - Bhathena, H M (Acta chirurgiae plasticae, 2002)
During the course of head and neck surgery for cancer the reconstructive surgeon is involved in replacement of pharyngeal mucosal defects. Siedenberg (7) first reported free transplantation in 1959 using a segment of jejunum, Roberts (5) using jejunum, Nakayama (3) using colon and Jurkiewicz (4) using ileum and jejunum. Green (2) in 1966 using microsurgical techniques demonstrated 100% survival of free transfers of jejunum and also patches of jejunum in dogs. We have used free interposing iso-peristaltic jejunal loop transfer in 30 patients to bridge the cervical esophagus defects for advanced cancer of hypopharynx, larynx and cervical esophagus after ablative cancer surgery. The major complication rate was 13% (4/30 cases) including total flap failure and loss of interposed jejunal segment. The minor complication rate was 36% (11/30 cases) including postoperative hypothyroidism in 2 patients. Intra-abdominal hemorrhage or peri-operative mortality was not observed in any of our cases. Total post-operative average hospital stay was 15 days, and median swallowing time was 10 days. Complication rates and success of early functional and social restoration have been analyzed.
Keywords: Postoperative Complications; Male; lidé; Pharynx; nádory hrtanu; Esophageal Neoplasms; jejunum; Humans; farynx; ezofágoplastika; nádory hypofaryngu; Esophagoplasty; mužské pohlaví; nádory jícnu; pooperační komplikace; Hypopharyngeal Neoplasms; ženské pohlaví; Female; Jejunum; Laryngeal Neoplasms